2001
DOI: 10.4141/p99-176
|View full text |Cite
|
Sign up to set email alerts
|

Impact of one year crozier removal on long-term frond production in Matteuccia struthiopteris

Abstract: Bergeron, M. E. and Lapointe, L. 2001. Impact of one year crozier removal on long-term frond production in Matteuccia struthiopteris. Can. J. Plant Sci. 81: [155][156][157][158][159][160][161][162][163]. Matteuccia struthiopteris (L.) Todaro populations that had been subjected to crozier harvesting over the past 25 yr were investigated. The number of crowns harvested and the number of croziers harvested per crown varied annually, but most crowns were harvested at least once over 5 yr. In 1995, total and 50% de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…A higher number of rootstocks measuring less than 2 cm in diameter was reported in areas where the canopy cover was 30 % lower in comparison with the remaining quadrats (t =- 3.07, P = 0.003). Similar results were reported by Prange and von Aderkas (1985), von Aderkas and Green (1986), and Bergeron and Lapointe (2001). A study by Kołos and Wanaks (2008) showed that M. struthiopteris in the Kulikówka valley was larger in shady areas than in full sunshine.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A higher number of rootstocks measuring less than 2 cm in diameter was reported in areas where the canopy cover was 30 % lower in comparison with the remaining quadrats (t =- 3.07, P = 0.003). Similar results were reported by Prange and von Aderkas (1985), von Aderkas and Green (1986), and Bergeron and Lapointe (2001). A study by Kołos and Wanaks (2008) showed that M. struthiopteris in the Kulikówka valley was larger in shady areas than in full sunshine.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies on Matteuccia struthiopteris populations revealed that an increased fertility rate was correlated with direct light availability (Prange and von Aderkas 1985;von Aderkas and Green 1986;Bergeron and Lapointe 2001). The fertility rate of populations directly exposed to sunlight was higher than in populations growing under a dense canopy (Prange and von Aderkas 1985;von Aderkas and Green 1986;Bergeron and Lapointe 2001). Ostrich fern finds optimum growth conditions at a density of the canopy of upper layers of plants of 20 % (Odland et al 2006).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to Ellenberg et al (1991), M. struthiopteris has an indicator light value of five which is characteristic for semi shade plants, and this is in accordance with Prange (1980), who maintains that it is a typical shade-adapted plant. Condition of direct sunlight has been found to increase its fertility rate (Prange and von Aderkas 1985;von Aderkas and Green 1986;Bergeron and Lapointe 2001) as compared with a dense canopy. Donelan and Corey (1994) found a decreased survival of plants with increasing light intensity, and Dykeman (1981) found in an experimental study that M. struthiopteris responded positively to reduced light.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that the species' health can be significantly affected by the removal of young fronds. Bergerson and Lapointe (2001) conducted a five-year study in Québec, Canada, investigating the impacts of harvesting on Matteuccia struthiopteris. They found that harvesters should collect no more than half the croziers produced by a shoot, as removal of all shoots in a single year impaired carbohydrate accumulation and crozier production in subsequent years.…”
mentioning
confidence: 99%